Analysis of Greenhouse Gases and Odor Levels in the Sumompo TPA, Manado City, North Sulawesi - Bobby ., Polii; Jemmy ., Najoan; Tommy Ogie (AGRI-SOSIOEKONOMI, 2021)
The research aimed to know the level of odor by hydrogen sulfide (H2S) and ammonia (NH3) gases, as well as to determine the level of greenhouse gases pollutant carbon monoxide (CO), sulfur dioxide (SO2), nitrogen dioxide (NO2) at the Sumompo Waste Landfill, Manado City, North Sulawesi. This research was conducted at the TPA Sumompo, City of Manado and laboratory analyses at Agriculture Faculty from August to November 2020. The study was conducted by measuring parameters of gas greenhouse: sulfur dioxide (SO2), carbon monoxide (CO), nitrogen dioxide (NO2), and the gas causes the smell of ammonia (NH3) and hydrogen sulfide (H2S) at the Manado Sumompo Trash Landfill (TPA) and then analyzed at the PT Global Quality Analytical Laboratory. The research showed that The level of odor pollution of H2S and NH3 gases at the Sumompo TPA showed that ammonia (NH3) has generally passed the quality standard, while the hydrogen sulfide (H2S) has approached the threshold of standard quality. Then, the sulfur dioxide (SO2) gas pollution varied from 66.2 to 73.8 µg/Nm3, and all of which were still below the SO2 quality standard of 900 µg/Nm3.  The carbon monoxide (CO) gas ranged from 1680 to 2460 µg/Nm3, all of which are below the quality standard of CO 30,000 µg/Nm3, and for nitrogen dioxide (NO2) varied from 61.4 to 76.3 µg/Nm3, all of which were below the NO2 quality standard of 400 µg/Nm3.*mjp*